2017
DOI: 10.1038/s41598-017-15997-z
|View full text |Cite
|
Sign up to set email alerts
|

Features of reactive cysteines discovered through computation: from kinase inhibition to enrichment around protein degrons

Abstract: Large-scale characterisation of cysteine modification is enabling study of the physicochemical determinants of reactivity. We find that location of cysteine at the amino terminus of an α-helix, associated with activity in thioredoxins, is under-represented in human protein structures, perhaps indicative of selection against background reactivity. An amino-terminal helix location underpins the covalent linkage for one class of kinase inhibitors. Cysteine targets for S-palmitoylation, S-glutathionylation, and S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 72 publications
(91 reference statements)
0
16
0
Order By: Relevance
“…Lysine motifs for S-nitrosylation have been reported previously; lysine motif 1 (Lys at position −2) was found in a screen for endogenously SNO-Ps in macrophages (38), and lysine motif 2 (Lys at position +6) was identified in a screen on GSNO-treated heart homogenates (25). The mechanisms through which lysine motifs regulate S-nitrosylation of MBD3 and HDAC2 are not currently known; however, a recent bioinformatic analysis suggested that cysteines in close proximity to ubiquitylated lysines are more likely to be modified by S-nitrosylation (39), hinting at a possible interplay between cysteine S-nitrosylation and posttranslational modifications at neighboring residues. Our screen provides targets of nuclear S-nitrosylation in cortical neurons, the site(s) of S-nitrosylation for most identified proteins, and characterization of lysine-containing motifs that regulate cysteine S-nitrosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Lysine motifs for S-nitrosylation have been reported previously; lysine motif 1 (Lys at position −2) was found in a screen for endogenously SNO-Ps in macrophages (38), and lysine motif 2 (Lys at position +6) was identified in a screen on GSNO-treated heart homogenates (25). The mechanisms through which lysine motifs regulate S-nitrosylation of MBD3 and HDAC2 are not currently known; however, a recent bioinformatic analysis suggested that cysteines in close proximity to ubiquitylated lysines are more likely to be modified by S-nitrosylation (39), hinting at a possible interplay between cysteine S-nitrosylation and posttranslational modifications at neighboring residues. Our screen provides targets of nuclear S-nitrosylation in cortical neurons, the site(s) of S-nitrosylation for most identified proteins, and characterization of lysine-containing motifs that regulate cysteine S-nitrosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of paramount importance that a precise knowledge of the factors that influence the reactivity of these residues is obtained [ 1 , 2 ]. It is a common opinion (universally accepted) that this is mainly controlled by their p K a and by the accessibility of a given reagent [ 1 , 3 , 4 , 5 , 6 , 7 ]. In fact, the sulfhydryl group of cysteines is almost inert in its protonated form (except in free-radical reactions), while the thiolate form is the true reactive form.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, computational studies by Roos and co-workers emphasized that this stabilization is mostly promoted by hydrogen bonds at the N-terminus of α-helices, and it seems to be more pronounced with a larger number of turns in the helix (Roos et al, 2006). In addition, a recent computational study also emphasized that Cys residues closer to the N-terminus of α-helices often exhibit lower pK a s and higher nucleophilicity (Fowler et al, 2017).…”
Section: Alpha-helixmentioning
confidence: 99%